Relay intercropping of maize with common dry beans to rationalize nitrogen fertilizer - El-Mehy, Amira A.; Shehata, Manal A.; Mohamed, Ahmed S.; Saleh, Said A.; Suliman, Ahmed A. (Frontiers in Sustainable Food Systems, 2023)
Two field experiments were performed during the years of 2020 and 2021 at Sers El-Layian Station, northern Egypt. The current study aiming to study the effect of three sowing dates of maize, represent 3 co-growth duration, (T1: at flowering stage (FS) of common beans, (60 days co-growth duration), T2: 15 days after FS (45 days co-growth duration) and T3: 30 days after FS (30 days co-growth duration with beans) and three N fertilizer levels (N1: 190.4, N2: 238.0 and N3: 285.6 kg N/ha of maize) on productivity, profitability and N fertilizer rationalization. The longest co-growth duration of maize intercropping with common beans (T1) significantly (P≤0.05) decreased common beans and maize yields compared with T2 and T3. Performance of common beans did not show (P≤0.05) any variation under different N fertilizer levels of maize. Significant (P≤0.05) increase in maize yield and its components with raising N fertilizer level up to N3. Although there was no significant variation in maize yield when applied N2 and N3, however, nitrogen use efficiency (NUE) was significant (P≤0.05) higher in N2 than N3 by 18.34%. Regardless of planting time and N fertilizer level of maize, combined productivity of common beans and maize increased in the intercropped system as cleared by higher total land equivalent ratios (LER) and area time equivalent ratios (ATER). Highest LER value 1.99 was observed at the shortest co-growth period T3 under N3 followed by 1.97 with N2. Positive values in the actual yield loss index (AYL) indicated intercropping advantage. Different competition indices showed a greater dominance of maize over common beans (aggressivity, Ag; competitive ratio, CR; actual yield losses, AYL). However, the intercropping systems increased the economic advantage (intercropping advantage index, IAI and monetary advantage index MAI) over monoculture. These results imply that shortening the period of co-growth maize with common beans (T3) and applying 238.0 kg N/ha in the relay intercropping system reduced mineral N fertilizer use by 16.67% compared to the advised level 285.6 kg N/ha along with increased productivity per unit area and economic advantages for small-farmer.